2020
DOI: 10.1002/adma.202002450
|View full text |Cite
|
Sign up to set email alerts
|

Preintercalation Strategy in Manganese Oxides for Electrochemical Energy Storage: Review and Prospects

Abstract: the past decades, some issues of MnO 2based cathodes still remain due to the low electronic conductivity, [19-21] low utilization of reversible discharge depth, [22,23] sluggish diffusion kinetics, [24-26] and poor structural stability upon cycling, [27-29] which restricts their practical application in the commercial secondary batteries. Taking the Zn-ion batteries as example, the MnO 2 cathode seriously suffer from the above issues, especially the sluggish Zn 2+ diffusion, [30] and structural collapse issue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 157 publications
(88 citation statements)
references
References 151 publications
(241 reference statements)
1
83
0
Order By: Relevance
“…A decent specific capacity of 84 mAh g −1 was measured after 1000 cycles; as a result of the fast charge/ discharge rate, the capacity retention was improved to reach 91% at the 1000th cycle. This cycling stability compare positively to most of the reported δ-MnO 2 materials for Zn-ion batteries (see Table S1, Supporting Information), [19][20][21][23][24][25] and similar to the previously reported other ions pre-intercalated MnO 2 as cathode for Zn-ion batteries as shown in Table S2, Supporting Information. [9,11,17,18,24,33] The good cycling stability could be explained by the pre-intercalated K + and H 3 O + in the KMO structure, as a result of charge balancing, [28] which acts as pillars to stabilize the layered structures.…”
Section: Electrochemical Characterizationssupporting
confidence: 89%
See 2 more Smart Citations
“…A decent specific capacity of 84 mAh g −1 was measured after 1000 cycles; as a result of the fast charge/ discharge rate, the capacity retention was improved to reach 91% at the 1000th cycle. This cycling stability compare positively to most of the reported δ-MnO 2 materials for Zn-ion batteries (see Table S1, Supporting Information), [19][20][21][23][24][25] and similar to the previously reported other ions pre-intercalated MnO 2 as cathode for Zn-ion batteries as shown in Table S2, Supporting Information. [9,11,17,18,24,33] The good cycling stability could be explained by the pre-intercalated K + and H 3 O + in the KMO structure, as a result of charge balancing, [28] which acts as pillars to stabilize the layered structures.…”
Section: Electrochemical Characterizationssupporting
confidence: 89%
“…[17,18] It has been reported that the preintercalation of large cations (such as, K + , Ce 3+ , and Ca 2+ ) in MnO 2 during synthetic process can stabilize the structure through coordination of guest-ions with adjacent host atoms. [16,[19][20][21][22][23][24][25] Moreover, the preintercalation of alkaline ion strategy in MnO 2 has also attracted much attention as an effective approach to enhance the electronic conductivity, activating more active sites, and promoting diffusion kinetics. [25] To date, various types of reaction mechanisms have been reported for Mn oxide-based positive electrode of Zn-MnO 2 battery in Zn-containing aqueous electrolyte.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Metal substitution control is a general method to tune the electrochemical performance of electrodes. [ 100 ] For the most widely used PBA materials (A x M[Fe(CN) 6 ] y · n H 2 O), there exist two type of transition metal ions in the lattice framework. When M is a transition metal such as Ni, Cu, Zn, N‐coordinated M is electrochemically inert, and only C‐coordinated Fe 2+ can undergo redox conversion.…”
Section: Optimization Strategies For High‐performance Pba Cathodesmentioning
confidence: 99%
“…Currently, tunnel α‐MnO 2 and layered δ‐MnO 2 are considered to be the most investigated MnO 2 polymorphs as ZIB cathode, due to their unique structure that can accommodate the Zn 2+ storage [26,40] . However, pristine Mn‐based oxides typically exhibit poor cyclic stability, poor rate performance, and unsatisfactory capacity, which results in the increasing urgency for the implementation of modification strategies, such as interlayer engineering, defect engineering, hybridization, or heteroatom incorporation, to improve the electrochemical performance [2,41–47] . Despite the significant research effort devoted in the development of Mn‐based oxides with the various modification strategies, the lack of clear comparison in the electrochemical performance across the various Mn‐based oxides may lead to the contemplations in the advantages of employing the respective Mn‐based oxide.…”
Section: Introductionmentioning
confidence: 99%